A importância das abelhas na visão de diferentes segmentos da cadeia produtiva do maracujá (Passiflora spp) - Sussi, Juliano Schiavo (Universidade Federal de São Carlos, 2017)
This work aims to evaluate the perception of the different segments of the passion fruit production chain (Passifloraceae edulis) regarding the importance of bees. This agricultural culture is responsible for generating three to four direct jobs and seven to eight indirect jobs in the production chain. Although passion fruit produces hermaphrodite flowers, this plant has mechanisms that prevent self-fertilization - which necessitates the presence of pollinating biotic agents or artificial pollination. Knowing that the natural pollinators of this culture are medium to large bees, and to verify if people knew about it, 162 people were interviewed in 30 cities in Brazil, divided into five segments: Agricultural Input Sellers, Farmers, Primary and Secondary Buyers and Final Consumers. For the analyzes, response frequencies and correspondence analysis were used. It was verified that the Farmers and Input Sellers present greater knowledge about pollination and pollinators, perceive the bees in a positive way and know the importance of large bees for pollination of passionflower flowers. Although farmers know the importance of bees, few adopt friendly practices for these beings. Already the segments related to the sale and consumption of passion fruit have less knowledge about pollination and perceive the bees in a negative way. Respondents, in general, also observe a decline in the number of pollinators, and most believe that this deficit is related to the destruction of green areas, global warming, diseases that affect bees and the use of pesticides.
The importance of bees in view of different segments of the production chain of passion fruit (Passiflora spp)
Keywords: Polinização; Serviço ecossistêmico; Produção agrícola; Xylocopa; Pollination; Ecosystem service; Agricultural production; CIENCIAS AGRARIAS